1981
DOI: 10.1037/0022-006x.49.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation of the Jesness Inventory with delinquents and nondelinquents.

Abstract: Using the Jesness Inventory (JI), personality patterns of two levels of institutionalized delinquents, those formally adjudicated by the courts for two or more charges and those not formally charged, were compared with a socially actingout group and a matched control group. The Asocial Index of the JI was significant across and between all groups with a progressive increase in T scores directly related to delinquent involvement. The JI scales of Social Maladjustment, Value Orientation, Autism, Manifest Aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…Previous research has demonstrated that the Jesness discriminates delinquent from nondelinquent youth and predicts future delinquent activity in previously nonoffending youth (e.g. Kunce & Hemphill, 1983;Martin, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that the Jesness discriminates delinquent from nondelinquent youth and predicts future delinquent activity in previously nonoffending youth (e.g. Kunce & Hemphill, 1983;Martin, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Investigações de verificação da adaptabilidade do instrumento a outros contextos socioculturais foram realizadas junto à população inglesa (Fisher, 1967;Martin, 1981e Saunders & Davies, 1976, escocesa (Vallance & Forrest, 1971), indiana (Singh, 1978(Singh, , 1980(Singh, , 1983, norte-irlandesa (Harbison, Jardine & Curran, 1978), neozelandesa (Howard, 1981), canadense (Lagier & Dickner, 1988;LeBlanc, McDuff & Tremblay, 1994e Shivrattan, 1988 e australiana (Kahn & Fua, 1995;Putniņš,1980).…”
Section: Personalidade Adolescência E "Delinquência Juvenil"unclassified
“…Em um dos estudos que testou a aplicabilidade do instrumento na população inglesa, indicou-se que as escalas de DS, OV, Al e AM foram capazes de diferenciar níveis de deliquência e predizer a reincidência para determinados jovens, ou seja, persistência na prática de delitos (Saunders & Davies, 1976 (Martin, 1981).…”
Section: Personalidade Adolescência E "Delinquência Juvenil"unclassified
See 2 more Smart Citations